2021
DOI: 10.1108/jpbafm-06-2020-0091
|View full text |Cite
|
Sign up to set email alerts
|

Accountability in times of exception: an exploratory study of account-giving practices during the early stages of the COVID-19 pandemic in Italy

Abstract: PurposeThe purpose of this paper is to explore the role of accountability in times of exception. The Italian government's account-giving practices are critically analysed with respect to the distinct modes in which duties of accountability are discharged for the exceptional measures taken during the early stages of the COVID-19 pandemic outbreak in early 2020.Design/methodology/approachThis paper draws on an exploratory case study. The case analysis draws primarily on data obtained through publicly available d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…Because of the pandemic and the consequential restrictions imposed by national governments, socially distanced practices gained prominence (Andreaus et al, 2021). More…”
Section: Online Accountabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the pandemic and the consequential restrictions imposed by national governments, socially distanced practices gained prominence (Andreaus et al, 2021). More…”
Section: Online Accountabilitymentioning
confidence: 99%
“…The Covid-19 pandemic created the biggest humanitarian crisis in decades and did not distinguish between rich and poor communities (World Health Organization, 2020; Arun et al ., 2021). As the focus at the start of the pandemic was on national governments and their capabilities to deal with the pandemic, studies on public accountability have dominated discussion in the scholarly community (Andreaus et al ., 2021). However, the impact of the pandemic was not limited to national governments.…”
Section: Introductionmentioning
confidence: 99%
“…Also the accountability styles were affected by the management of COVID-19 pandemic has it evolved. Andreaus et al (2021), analyzing the Italian case, observed how the central government employed various accountability styles, from rebuttal and dismissal, to reactive, proactive and coactive, in relation to its conduct and to the distinctive relationships with social actors (Andreaus et al, 2021).…”
Section: Accounting For Unstable Environmentsmentioning
confidence: 99%
“…Management control is a process influenced by the organization's supervisory body, top management (management), and other employees designed to provide reasonable assurance about the achievement of objectives in the following categories: (a) Effectiveness and efficiency of activities, (b) Reliability of financial reporting, (c) Compliance with applicable rules and regulations (Anthony and Govindarajan, 2005). Research conducted by Paramitha & Gayatri (2016) and Rininda & Sudaryati (2020) researched public sector management control and found the results that the public sector management control system had a positive effect on SKPD performance accountability, meaning that public sector managerial control was running optimally and could improve accountability aspects of SKPD performance.…”
Section: Introductionmentioning
confidence: 99%